INTERFAITH COEXISTENCE: INTOLERANCE, ATTACKS, RELIGIOUS RACISM, AND RESISTANCE IN THE VOICES OF PARTICIPANTS OF THE XVII WALK FOR RELIGIOUS FREEDOM IN RIO DE JANEIRO" - Silva, Paulo Henrique Prado da; Ribeiro, Natália Rodrigues Codeço (Cadernos do Desenvolvimento Fluminense, 2025)
This work examines how religious violence experiences vary according to creed, racialization, and practices of participants in the XVII Walk for Religious Freedom, held in Rio de Janeiro. Based on semi-structured interviews and literature review, the findings reveal that African and Indigenous-rooted religions face the highest levels of violence, including physical attacks and destruction of sacred spaces. Hegemonic religions, such as Catholicism, experience symbolic discrimination but are not exempt from interdenominational tensions. The Walk emerged as a symbolic space for resistance and interfaith dialogue amidst growing fundamentalism. The work highlights the importance of integrating Rio de Janeiro’s cultural history into school curricula to foster understanding and respect. It also proposes hosting interfaith events with inclusive outreach and infrastructure to strengthen solidarity networks. These actions are crucial for mitigating religious inequalities and fostering a more peaceful and plural coexistence.